2007
DOI: 10.3808/jei.200700090
|View full text |Cite
|
Sign up to set email alerts
|

Overall Heat Transfer Coefficients in Organic Substrates Composting

Abstract: ABSTRACT. The overall heat-transfer coefficients for four self-heating composting experiments were determined and mathematically modeled based on an energy balance approach. Heat dissipation to the surroundings through combined conductive/convective/radiative heat transfer mechanisms has been considered. Energy balance parameters were mathematically modeled with time for the data collected for the composting of mixed yard/green vegetables wastes, broiler litter and bagasse in PVC drum composters. The rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 48 publications
3
6
0
Order By: Relevance
“…The physical properties of compost sample in this study can be considered as mature. As other studies also found that compost with odorless, a fine texture and dark colour is matured compost (33). This study also found that short period formation of compost compared to traditional method was due to the precomposting process applied during the first period of the study in which the minimization process from grinding caused the large particles into smaller pieces.…”
Section: Color Texture and Odorsupporting
confidence: 51%
“…The physical properties of compost sample in this study can be considered as mature. As other studies also found that compost with odorless, a fine texture and dark colour is matured compost (33). This study also found that short period formation of compost compared to traditional method was due to the precomposting process applied during the first period of the study in which the minimization process from grinding caused the large particles into smaller pieces.…”
Section: Color Texture and Odorsupporting
confidence: 51%
“…Oxygen and carbon dioxide inflows were determined by the air flow and standard air composition. The overall heat transfer of the surface (UA) was determined using the surface area of the compost mixture and a standard value for the U coefficient (Mudhoo and Mohee, 2007) which was within the range of 238-720 kJ/d°C reported in the literature (Kaiser, 1996;Zhang et al, 2010). Note that this term can be useful in designing of composting systems, since can predict the wall losses of the heat and thus could lead to the selection of the proper surface area of the compost.…”
Section: Model Inputsmentioning
confidence: 99%
“…According to the reported number for the thermal capacity of the SMC and water in references (Mudhoo & Mohee, 2007), the thermal capacity (C) of the solution inside the reactor was calculated at 3.56 (Kj/Kg K). Here, m is the mass of the materials inside the reactor and is equal to 24,000 kg, T s is the inside temperature and is equal to 35°C or 55°C, and T in is the initial temperature of the substrate.…”
Section: Heat Transfer In the Designed Reactormentioning
confidence: 99%